Overview of Mother's Knowledge About Foremilk Balance And Hindmilk in 0-6 Months Old Babies at the Primary Clinic Sunggal Medan 2021 - Efrida Yanti Siregar (Jurnal Kesehatan LLDikti Wilayah 1 (JUKES), 2022)
The mortality rate is the first indicator to determine the level of health of children, because as a guide according to child health, which is now a problem that often occurs in the health sector in Indonesia. Breastfeeding is a way to reduce the high number of infant deaths because breast milk has all the ingredients needed by babies. The duration of breastfeeding is very important so that the foremilk and hindmilk can be consumed by the baby. The imbalance of foremilk and hindmilk, the baby will feel discomfort and pain then become fussy. This research is descriptive in nature with the aim of knowing the description of mother's knowledge about giving foremilk and hindmilk to infants aged 0-6 months. The population of this study were 30 mothers. Sampling using a total sampling technique as many as 30 people. The time of data collection was carried out on April 22 - June 30, 2021 with interviews using a questionnaire. The results showed that the majority of respondents aged 19-25 years were 14 people (46.7%), the minority of respondents aged 31-38 years was 5 people (16.6%). The majority of respondents had 20 high school education (66.7%), the minority of respondents did not go to school 2 people (6.7%). The majority of respondents work as housewives with 25 people (83.3%), and the minority of respondents whose jobs are as employees of 2 people (6.7%). The majority of respondents have sufficient knowledge of 15 people (50.0%), the minority of respondents have good knowledge of 6 people (20.0%). The results showed that the majority of respondents aged 19-25 years were 14 people (46.7%), the minority of respondents aged 31-38 years was 5 people (16.6%). The majority of respondents had 20 high school education (66.7%), the minority of respondents did not go to school 2 people (6.7%). The majority of respondents work as housewives with 25 people (83.3%), and the minority of respondents whose jobs are as employees of 2 people (6.7%). The majority of respondents have sufficient knowledge of 15 people (50.0%), the minority of respondents have good knowledge of 6 people (20.0%). The results showed that the majority of respondents aged 19-25 years were 14 people (46.7%), the minority of respondents aged 31-38 years was 5 people (16.6%). The majority of respondents had 20 high school education (66.7%), the minority of respondents did not go to school 2 people (6.7%). The majority of respondents work as housewives with 25 people (83.3%), and the minority of respondents whose jobs are as employees of 2 people (6.7%). The majority of respondents have sufficient knowledge of 15 people (50.0%), the minority of respondents have good knowledge of 6 people (20.0%). and the minority of respondents work as employees of 2 people (6.7%). The majority of respondents have sufficient knowledge of 15 people (50.0%), the minority of respondents have good knowledge of 6 people (20.0%). and the minority of respondents work as employees of 2 people (6.7%). The majority of respondents have sufficient knowledge of 15 people (50.0%), the minority of respondents have good knowledge of 6 people (20.0%).